2022
DOI: 10.1101/2022.12.08.22283232
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reliable and generalizable brain-based predictions of cognitive functioning across common psychiatric illness

Abstract: A primary aim of precision psychiatry is the establishment of predictive models linking individual differences in brain functioning with clinical symptoms. In particular, cognitive impairments are transdiagnostic, treatment resistant, and contribute to poor clinical outcomes. Recent work suggests thousands of participants may be necessary for the accurate and reliable prediction of cognition, calling into question the utility of most patient collection efforts. Here, using a transfer-learning framework, we tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 100 publications
0
2
0
Order By: Relevance
“…The datasets in the current study comprised relatively healthy participants. Meta-matching might be potentially useful for psychiatric populations (Chopra et al, 2022). Including psychiatric datasets to the base model training might further improve generalization to new datasets by increasing the diversity of the source datasets.…”
Section: Discussionmentioning
confidence: 99%
“…The datasets in the current study comprised relatively healthy participants. Meta-matching might be potentially useful for psychiatric populations (Chopra et al, 2022). Including psychiatric datasets to the base model training might further improve generalization to new datasets by increasing the diversity of the source datasets.…”
Section: Discussionmentioning
confidence: 99%
“…New methods for external replication, such as meta-matching, have shown promise in leveraging neural network models that were trained using large samples that could be applied to behavioral prediction in smaller samples (Chopra et al 2022. Recently, metamatching was trained on the UK Biobank and then applied to small clinical samples where large data sets are not possible (Chopra et al 2022. It was found that meta-matching increased the prediction of brain connectivity to cognitive function.…”
Section: Replication Testingmentioning
confidence: 99%